The Italian long-term program submitted to the O.E.E.C. - TREMELLONI, R. (PSL Quarterly Review, 2014)
The article sums up and comments on the Italian Long-Term Program submitted to the O.E.E.C., showing its specific targets, the premises on which it is based, and the lines to be followed in carrying it out. The author calls attention to the fact that the structural features of the Italian economy create a more difficult situation than that prevailing in the other participating countries. He illustrates the main lines of the economic policies the Government purposes following in the next few years, indicating the targets the plan has in view in their fundamental characteristics and in the several branches of economic activity without disguising the difficulty of coordinating them with the plans of other O.E.E.C. countries. The last part of the article stresses once more the problem of unemployment, on whose solution, in the last resort will depend on the success of the whole program and the possibility of securing a stable and lasting equilibrium. JEL: F15, E24, E61